2006
DOI: 10.1016/j.maturitas.2006.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Conventional-dose hormone therapy (HT) and tibolone, but not low-dose HT and raloxifene, increase markers of activated coagulation

Abstract: Our data suggest that low-dose HT is associated with less activation of coagulation than conventional-dose HT. This finding may be of clinical importance since randomized clinical trials showing increased risk of thrombosis have utilized conventional-dose HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 137 publications
(151 reference statements)
4
29
1
1
Order By: Relevance
“…The unavailable information on estrogens doses was also a limitation of our study. Although increasing doses of estrogens may increase the coagulation activation, 43 observational studies have suggested no significant difference in thrombotic risk by estrogen dose. 12,19,20,22,23 However, studies with high level of evidence comparing estrogen doses effect on thrombotic risk are still lacking.…”
Section: Canonico Et Almentioning
confidence: 99%
“…The unavailable information on estrogens doses was also a limitation of our study. Although increasing doses of estrogens may increase the coagulation activation, 43 observational studies have suggested no significant difference in thrombotic risk by estrogen dose. 12,19,20,22,23 However, studies with high level of evidence comparing estrogen doses effect on thrombotic risk are still lacking.…”
Section: Canonico Et Almentioning
confidence: 99%
“…Two studies consistently showed that tibolone would have the same or a less deleterious effect on F1+2 and DDimers than did CEE or E2 combined with NETA [55,56,[59][60][61]. By contrast, data were more controversial regarding the comparison of the effects of tibolone and estrogens combined with NETA on APCr.…”
Section: Tibolonementioning
confidence: 99%
“…By contrast, data were more controversial regarding the comparison of the effects of tibolone and estrogens combined with NETA on APCr. While tibolone might more induced APCr than did estradiol and estriol, it could have less effect on haemostasis than did CEE [55,[59][60][61]. With regards to other progestogens, one study has investigated the differential effect of tibolone and CEE combined with micronized progesterone on haemostasis and showed that increase in F1+2 was more pronounced among HT users compared to tibolone ones [57].…”
Section: Tibolonementioning
confidence: 99%
“…Studies evaluating the effects of tibolone on the coagulation system are sparse and showed discordant results (Eilertsen et al 2006). Either potentially favorable effects or no changes were observed in some risk markers for venous thromboembolism, whereas other markers showed procoagulatory changes.…”
Section: Effects On Coagulationmentioning
confidence: 99%